Peran Spiritualitas dalam Membentuk Karakter Peserta Didik di Era Digital: Perspektif Pendidikan Karakter - Ramadhaniyah, Monica - (Maliki Interdisciplinary Journal, 2026)
This study explores the role of spirituality in shaping students’ character in the digital era, marked by rapid technological growth, unlimited access to information, and shifting social interactions. Using a descriptive qualitative approach, this study reviews recent literature related to spiritual values, character education, and the challenges posed by digital development on adolescent behavior. The findings reveal that spirituality functions as an internal foundation that fosters integrity, empathy, discipline, and responsibility, while also serving as self-control in navigating digital technology. Spiritual values support balanced character formation by strengthening both cognitive abilities and emotional intelligence through worship practices, self-reflection, and teacher role modelling. Within educational settings, integrating spirituality into learning activities, guidance programs, and religious school environments helps reduce negative digital impacts and reinforces students’ moral identity. These results highlight spirituality’s continued relevance as a pillar of adaptive character formation amid the dynamics of the digital age.